(untitled) (REVISTA SAYWA, 2024)
In a brief interview, we had the opportunity to speak with Professor Carlos Andrés Gómez Vasco, an outstanding professional with a degree in Physics from the Universidad Distrital Francisco José de Caldas. Professor Gómez Vasco is distinguished in his field by his deep knowledge in physics experimentation, his ability to share his knowledge with his colleagues and his dedication to the technification of laboratories nationwide. In this conversation, Saywa had the opportunity to explore his experience and perspectives in the world of physics and research.